Targeting Cell Death: Pyroptosis, Ferroptosis, Apoptosis and Necroptosis in Osteoarthritis - Jian Yang; Jian Yang; Jian Yang; Shasha Hu; Yangyang Bian; Yangyang Bian; Yangyang Bian; Jiangling Yao; Jiangling Yao; Jiangling Yao; Dong Wang; Xiaoqian Liu; et al. (Frontiers in Cell and Developmental Biology, 2022)
New research has shown that the development of osteoarthritis (OA) is regulated by different mechanisms of cell death and types of cytokines. Therefore, elucidating the mechanism of action among various cytokines, cell death processes and OA is important towards better understanding the pathogenesis and progression of the disease. This paper reviews the pathogenesis of OA in relation to different types of cytokine-triggered cell death. We describe the cell morphological features and molecular mechanisms of pyroptosis, apoptosis, necroptosis, and ferroptosis, and summarize the current research findings defining the molecular mechanisms of action between different cell death types and OA.